New cultural actors in the Costa Rican musical tradition: La Cimarrona Palmareña (2014) - Varela Sancho, Antonio (2017)
The “cimarronas” emerged in Costa Rica from the military bands and the municipal philharmonics on the second half of the XIX century. They were groups of no more than eight members that gladdened local festivities or popular fairs. Since then, they wander along the streets together with local masquerades with a traditional repertoire of pasodobles and parranderas, among others. Towards the end of the XX century, this musical ensembles were less common and were formed predominantly by elderly people; however, from 2004 to the date of this research study they reemerge strongly hand- in- hand with young musicians.The “Cimarrona” has been little studied, that is why this article is based on oral history: observations within the cultural space, interviews to former and present-day members of cimarronas, audience reactions, and a collection of videos, photographs and audio recordings. To contextualize this study, academic publication about the arrivaland development of similar cultural expressions to our continent such as carnivals and their dance groups, popular religious festivities and traditional parades, has been examined. This paperwork, after having analyzed the existent information, oral and written, establishes how a new cultural character comes to life taking ownership of the cimarronas tradition. This refers to young musicians who